A record of four monopisthocotylean monogeneans on gills of three fish species from the Yemeni coastal water of the Red Sea - Al-Zubaidy, A.B. (Mesopotamian Journal of Marine Sciences, 2022)
A total of 210 fish specimens belonging to three species from the Red Sea, Yemeni coastal waters were examined for the infection with monopisthocotylean monogeneans during the period from October 2009 till May 2010. The results showed the occurrence of four species of monogeneans. These were Pseudolamellodiscus sphyraenae from Sphyraena barracuda, Cabellaria liewi from Pomadasys argenteus and both Chauhanellus indicus and C. chauhani from Plicofollis dussumieri. The occurrence of these monogeneans represents their first record from the Yemeni fishes of the Red Sea except C. indicus which is reported here for the second time.